A probability distribution model for SCFs in internally ring-stiffened tubular KT-joints of offshore structures subjected to out-of-plane bending loads. (1st April 2016) - Ahmadi, Hamid
Abstract: The stress concentration factor (SCF) is one of the principal inputs in the fatigue reliability analysis of tubular joints. The SCF shows substantial scatter that highlights the necessity of deriving its governing probability function accurately. In the present research, results from 432 finite element (FE) stress analyses, verified against experimental data, were used to develop a probability distribution model for the SCFs in tubular KT-joints reinforced with internal ring stiffeners subjected to four types of out-of-plane bending (OPB) loads. Based on a FE parametric investigation, a sample database was prepared for the maximum chord-side SCFs of central and outer braces; and density histograms were generated for these samples. Nine different probability density functions (PDFs) were fitted to these histograms. The maximum likelihood method was used to determine the parameters of fitted distributions. In each case, using a developed computer code, Kolmogorov–Smirnov test was applied to assess the goodness of fit. Finally, the Generalized Extreme Value model was selected as the best-fitted distribution and after substituting the values of estimated parameters, six fully defined PDFs were proposed for the maximum chord-side SCFs of central and outer braces in internally ring-stiffened tubular KT-joints subjected to four types of OPB loading. Highlights: 432 FE analyses were carried out to study SCFs in ring-stiffened tubular KT-joints. Four types of OPB loading were considered for the parametric investigation. Results were used to develop a probability distribution model for maximum SCFs. The Generalized Extreme Value model was selected as the best-fitted distribution. Six PDFs were proposed for the maximum chord-side SCFs of central and outer braces.